Shekou : aux origines des zones économiques spéciales chinoises - Thierry Pairault (Revue de la Régulation)
The “Shekou Model” is a banner held up by one company – China Merchants – and used by Chinese propaganda to tout the success of its special economic zones (SEZs) as a model for developing countries. In this paper, we will not look at what has been achieved both in China and abroad, but we question the conception and development of the Shekou Industrial Zone between 1977 and 1984 and find that the birth of the SEZs owes more to chance and a general desire for reform than to economic policy thinking, and that Deng Xiaoping certainly played a much more limited role than is generally reported.